KUALITAS SISTEM PELAYANAN NASABAH DI PEGADAIAN SYARIAH CABANG PASAR WAGE PURWOKERTO SELATAN - Nadiva Amelia Baetisalamah; Umdah Aulia Rohmah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
In an increasingly competitive global era, service quality is a crucial factor in building customer trust and loyalty. This study uses a qualitative approach to examine the quality of the customer service system at Pegadaian Syariah Cabang Pasar Wage, Purwokeroto Selatan. Data were collected through direct observation, documentation, and literature review to obtain an overview of the service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that, overall, the service system at Pegadaian Syariah Cabang Pasar Wage is functioning well. However, several challenges were identified, such as limited supporting facilities, relatively long waiting times during peak periods, and suboptimal communication of information to customers. These findings are expected to serve as input for management in efforts to enhance service quality and strengthen the image of Pegadaian Syariah in the eyes of the community.